Plant–microbe partnerships in 2020. Issue 5 (15th July 2016) - Mitter, Birgit; Pfaffenbichler, Nikolaus; Sessitsch, Angela
Summary: The plant holobiont comprises the plant and its associated microbiota, which interact with each other and determine holobiont functioning and plant performance. We have started to understand the complexity of the involved microorganisms and their interactions, however, we need more research on plant–microbiome interactions to understand holobiont functioning. By 2020 we expect that our knowledge on these interactions will have considerably increased facilitating crop management practices based on the interactions of the plant holobiont. Abstract : The plant holobiont and its interactions determine plant performance.